Pengaruh durasi paparan cahaya matahari terhadap kecepatan pertumbuhan awal tanaman kacang hijau (Vigna radiata) varietas lokal Sumatera Barat - Apriyoza, Wandra; Syamsurizal, Syamsurizal; Anggrama, Shalsa (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Sunlight is one of the crucial factors that can affect plant growth, including mung beans (Vigna radiata), which are an important agricultural commodity in Indonesia. This study aims to examine the effect of sunlight exposure duration on the early growth rate of mung beans (V. radiata) local variety from West Sumatra. This research is a quantitative experimental study with treatments including four sunlight exposure durations: control (no light), 4 hours (P1), 6 hours (P2), and 12 hours (P3) per day. The study is designed in a completely randomized design (CRD) with 4 replications. The observation parameters in this study include plant height, number of leaves, and leaf width as the main parameters. The results showed that the duration of sunlight exposure significantly affected the number of leaves during the early growth phase of mung beans, but did not significantly affect plant height and leaf width. The 12-hour sunlight exposure (P3) provided the best results, with an average plant height of 10.65 cm, 5 leaves, and a leaf width of 2.05 cm. Therefore, adjusting the duration of sunlight exposure is crucial, especially in increasing the number of leaves that contribute to the plant's initial photosynthesis process. These results can serve as a basis for determining the optimal light duration for the cultivation of mung beans in the early growth phase.